A screening type sodium ion battery positive electrode material and its preparation method and application

By introducing polymerized carbon precursors on the surface of the layered oxide positive electrode material and sintering and chemical vapor deposition, a screened carbon cladding layer is formed, which solves the problem of difficult to take into account both the circulation stability and the ion transfer rate of the positive electrode material in the prior art, and achieves excellent electrochemical performance with high capacity and high voltage.

CN119061374BActive Publication Date: 2025-03-14NAKUN CARBON SOURCE (TIANJIN) TECHNOLOGY CO LTD +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411548061.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-01
Publication Date
2025-03-14
Estimated Expiration
2044-11-01

AI Technical Summary

Technical Problem

In the prior art, the cycling stability and ion transfer rate of layered metal oxide positive electrode materials in sodium ion batteries are difficult to take into account, resulting in poor performance of the materials under high capacity and high voltage conditions.

Method used

By introducing a controllable polymerized carbon precursor on the surface of the layered oxide precursor, a composite precursor is formed, and the synthesis of the positive electrode material and the surface coated porous carbon layer is achieved through the sintering process. The pore size is further optimized through chemical vapor deposition technology to obtain a layered metal oxide positive electrode material of the screened carbon coated layer.

Benefits of technology

It has achieved excellent cycle stability and good ion transfer rate of the positive electrode material of sodium ion battery, and has high reversible sodium storage capacity and high first-time Coulomb efficiency, which can run stably for 4,000 cycles.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119061374B_ABST
    Figure CN119061374B_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of sodium ion batteries, and in particular to a screening type sodium ion battery positive electrode material and a preparation method and application thereof. A composite precursor is obtained by introducing a controllable polymerized carbon precursor on the surface of a layered oxide precursor, and then a sintering process is used to simultaneously realize the synthesis of the layered oxide positive electrode material and the surface coating of a porous carbon layer. Then, a layered oxide positive electrode material with a screening type carbon coating layer is further obtained by chemical vapor deposition technology. The material is used in the positive electrode of a sodium ion battery, and its reversible sodium storage capacity can reach 200 mAh / g, and its first coulombic efficiency can reach 93%. When the capacity retention rate is 80%, it can stably operate for 4000 cycles, and has excellent cycle stability and ion transmission rate. Compared with the prior art, the invention solves the problem that it is difficult to suppress the occurrence of side reactions on the positive electrode surface and the rapid transmission of ions in the prior art.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of sodium ion batteries, and in particular to a screening type sodium ion battery positive electrode material and a preparation method and application thereof. Background Art

[0002] Considering the uneven distribution of lithium resources in the earth's crust and the fact that the main lithium mineral resources are distributed in South America and Australia, my country's lithium-ion battery industry always faces potential safety risks in the supply chain. Sodium-ion batteries, due to their abundant resources, low cost, and superior low-temperature and fast-charging characteristics, can make up for the shortcomings of lithium-ion batteries in terms of high cold, wide temperature, and fast charging, and become a potential alternative to lithium-ion batteries. Especially in large-scale energy storage systems and electric vehicle power systems, sodium-ion batteries have shown broad application prospects.

[0003] Existing layered metal oxide cathode materials have the advantages of easy synthesis, stable and controllable structure, and can achieve high capacity and high voltage electrochemical characteristics through the selection and regulation of transition metal elements. They are the first choice for building high energy density sodium ion batteries. However, the preparation of high capacity and high voltage cathode materials is usually achieved by increasing the content of transition metals. However, transition metals such as Ni and Mn with Jahn-Teller effect will cause irreversible phase changes in the material structure, resulting in the dissolution of these transition metals, causing the loss of reversible capacity and affecting the stability of the electrochemical interface on the negative electrode side. At the same time, water molecules in the air and byproducts such as HF produced by the reaction between the electrolyte and the positive electrode surface will aggravate the dissolution of transition metals. These layered metal oxides often show poor cycle stability.

[0004] Although surface coating is the most effective strategy to inhibit direct contact between layered metal oxides and electrolytes and humid air, and the coating layer can serve as a buffer to maintain strain and volume expansion, among various coating materials, non-porous or less-porous carbon materials can effectively improve the conductivity of the electrode while inhibiting the occurrence of interface side reactions. However, in the prior art, conventional carbon-coated sintering methods cannot produce porous structures, and all obtained are non-porous or less-porous carbon coating layers. Although they can effectively inhibit the occurrence of surface side reactions and transition metal dissolution, they cannot finely limit the pore size and do not have good ion rapid transmission characteristics, which will bring high transmission impedance and affect the performance of the material rate performance. It is difficult to provide a good ion transmission rate while effectively inhibiting the occurrence of surface side reactions and transition metal dissolution. Summary of the invention

[0005] In order to solve the problem in the prior art that it is difficult to simultaneously suppress the occurrence of side reactions on the surface of layered metal oxides and rapidly transport ions, the present invention provides a screening-type sodium ion battery positive electrode material and a preparation method and application thereof, wherein a composite precursor is obtained by introducing a controllable polymerized carbon precursor on the surface of a layered oxide precursor, and then a sintering process is used to simultaneously achieve the synthesis of the positive electrode material and the surface coating of a porous carbon layer, and then a chemical vapor deposition technology is used to further obtain a layered metal oxide positive electrode material with a screening-type carbon coating layer, which is used in the positive electrode of a sodium ion battery and has excellent cycle stability and ion transfer rate.

[0006] One aspect of the present invention is to provide a method for preparing a positive electrode material for a screening type sodium ion battery, including the preparation of a porous carbon-coated layered oxide positive electrode material and the preparation of a screening type sodium ion battery positive electrode material, wherein the porous carbon-coated layered oxide positive electrode material is prepared by subjecting a composite precursor of a layered oxide precursor and a carbon precursor to a heat treatment process, wherein the mass ratio of the layered oxide precursor to the carbon precursor is 1:1-1000:1; the temperature of the intermediate heat treatment is 600-1000°C;

[0007] The screening type sodium ion battery positive electrode material is prepared by a porous carbon-coated layered oxide positive electrode material through a chemical vapor deposition process, wherein the carbon source gas ventilation rate during the chemical vapor deposition process is 200-500 ml / min, the deposition temperature is 600-1000° C., and the reaction time is 30-240 min.

[0008] Furthermore, the layered oxide precursor is Na x TMO2 precursor, x≤1, M is at least one of Ni, Co, Fe, Mn, Cu, and Zn.

[0009] Further, the carbon precursor is at least one of phenolic resin, glucose, sucrose, polypropylene and polyacrylonitrile;

[0010] Preferably, the carbon precursor is in a state of a molten liquid or a solid powder.

[0011] Further, the method specifically includes the following steps:

[0012] Step 1: Stirring or impregnating a layered oxide precursor and a carbon precursor at a mass ratio of 1:1-1000:1 to obtain a composite precursor;

[0013] Step 2: placing the composite precursor obtained in step 1 in a tube furnace and performing heat treatment under a protective atmosphere of nitrogen or argon to obtain a porous carbon-coated layered oxide positive electrode material;

[0014] Step 3: Place the porous carbon-coated layered oxide positive electrode material obtained in step 2 in a chemical vapor deposition furnace, introduce a predetermined flow of nitrogen or argon, heat it to the deposition temperature, introduce the carbon source gas, and after the reaction is completed, cut off the carbon source gas, cool it down to room temperature under a protective atmosphere of nitrogen or argon to obtain the screening-type sodium ion battery positive electrode material.

[0015] Preferably, the impregnation and mixing process in step 1 is: the carbon precursor is configured into an aqueous solution at a concentration of 0.1-100M, and the layered oxide precursor is poured into the aqueous solution at a mass ratio of 1:1-1000:1 to the carbon precursor, and immersed for 6-48 hours, and the filter cake is dried after filtering to obtain a composite precursor.

[0016] Preferably, the heat treatment time in step 2 is 2-4 hours.

[0017] Furthermore, the specific surface area of ​​the porous carbon-coated layered oxide positive electrode material obtained in step 2 is 50 m 2 / g.

[0018] Furthermore, the carbon source gas in step 3 is at least one of acetylene, benzene vapor, toluene vapor, xylene vapor, ethylene, methane, propane, and natural gas.

[0019] Furthermore, the preparation method can also be used to prepare positive electrode materials of Prussian blue compounds, polyanion compounds and transition metal oxide screening type carbon coating layers.

[0020] Based on the above preparation method, the present invention provides a screening type sodium ion battery positive electrode material, which is a layered oxide positive electrode material with a screening type carbon coating layer.

[0021] Preferably, the specific surface area of ​​the sieve-type sodium ion battery positive electrode material is less than 5 m 2 / g, and the pore size is 0.3-0.5nm.

[0022] Another object of the present invention is to provide an application of a screening-type sodium ion battery positive electrode material in a sodium ion battery.

[0023] Preferably, the reversible sodium storage capacity of the screening-type sodium ion battery positive electrode material in the sodium ion battery is 150-200 mAh / g, and the first coulombic efficiency is greater than 90%.

[0024] The advantages of the present invention are:

[0025] 1. The present invention realizes the synthesis of positive electrode materials and surface coating of porous carbon layers simultaneously through a sintering process, and then fine-tunes the pore size through chemical vapor deposition technology to obtain a positive electrode material with a screening-type carbon coating layer, which has a reversible sodium storage capacity of up to 200 mAh / g and an initial coulombic efficiency of 93%. When the capacity retention rate is 80%, it can stably operate for 4000 cycles, and has excellent performance.

[0026] 2. The present invention realizes the design of a screening-type carbon coating layer by coating porous carbon on the surface of the positive electrode material and performing vapor deposition on the pores. Compared with the prior art, it can provide a good ion transmission rate while effectively suppressing the occurrence of surface side reactions and the dissolution of transition metals, thereby solving the problem in the prior art that it is difficult to simultaneously suppress the occurrence of positive electrode surface side reactions and rapid ion transmission. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 Schematic diagram of the preparation process of the screening type sodium ion battery positive electrode material according to Example 1 of the present invention;

[0028] Figure 2 This is a first cycle charge and discharge curve diagram of the screening type sodium ion battery positive electrode material of Example 1 of the present invention;

[0029] Figure 3 This is a test diagram of the cycle stability of the screening type sodium ion battery positive electrode material of Example 1 of the present invention;

[0030] Figure 4 It is a nitrogen adsorption-desorption isotherm diagram of the porous carbon-coated layered oxide positive electrode material of Comparative Example 2 of the present invention and the screening-type carbon-coated positive electrode material of Example 1. DETAILED DESCRIPTION

[0031] The following will be combined with the drawings in the embodiments of the invention to clearly and completely describe the technical solutions in the embodiments of the invention. Obviously, the described embodiments are only part of the embodiments of the invention, not all of them. Based on the embodiments in the invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the invention.

[0032] It should be noted that the various installation methods and technical terms mentioned in the invention are technical terms that have long been clearly known in the relevant technical field, so no further explanation is given. In addition, the same reference numerals are used for the same components, but this does not affect and should not constitute an accurate understanding of the technical solution by those skilled in the art.

[0033] Example 1 This example 1 provides a method for preparing a sieving type sodium ion battery positive electrode material, including the preparation of a porous carbon-coated layered oxide positive electrode material and the preparation of a sieving type sodium ion battery positive electrode material, such as Figure 1 As shown, the porous carbon-coated layered oxide positive electrode material is prepared by a composite precursor of a layered oxide precursor and a carbon precursor through a heat treatment process, and the screening type sodium ion battery positive electrode material is prepared by a porous carbon-coated layered oxide positive electrode material through a chemical vapor deposition (CVD) process, which specifically includes the following steps:

[0034] Step 1: Prepare a layered metal oxide precursor (the layered oxide precursor in this embodiment is Na x TMO2, x≤1, M is Ni, Co) and a carbon precursor (the carbon precursor in this embodiment is a phenolic resin in a solid powder state) are stirred and mixed at a mass ratio of 500:1 to obtain a composite precursor;

[0035] Step 2: placing the composite precursor obtained in step 1 in a tube furnace, and heat-treating it at 600° C. under a nitrogen atmosphere, to obtain a porous carbon-coated layered oxide positive electrode material after heat treatment for 3 h;

[0036] Step 3: Place the porous carbon-coated layered oxide positive electrode material obtained in step 2 in a chemical vapor deposition furnace, add 200 ml / min of nitrogen, raise the temperature to 900°C, introduce carbon source gas (the carbon source gas in this embodiment is methane), and the ventilation rate is 200 ml / min. After reacting for 90 minutes, cut off the carbon source gas, and cool down to room temperature under a protective atmosphere of nitrogen to obtain the corresponding screening-type sodium ion battery positive electrode material.

[0037] Example 2 The preparation method of the screening type sodium ion battery positive electrode material of this embodiment is the same as that of Example 1, except that the raw materials used and the parameter conditions involved in the preparation process are different (see Table 1). The mixing method of the precursor material in this embodiment is impregnation mixing, and the specific steps are:

[0038] Step 1: Prepare a carbon precursor in a 0.1M concentration into an aqueous solution (the carbon precursor in this embodiment is solid powdered glucose and sucrose), and prepare a layered metal oxide precursor (the layered oxide precursor in this embodiment is Na x TMO2, x≤1, M is Ni, Mn) is poured into an aqueous solution and immersed for 48 hours, and the filter cake is dried after filtering to obtain a composite precursor;

[0039] Step 2: placing the composite precursor obtained in step 1 in a tube furnace, and heat-treating it at 600° C. under a nitrogen atmosphere, to obtain a porous carbon-coated layered oxide positive electrode material after heat treatment for 2 h;

[0040] Step 3: Place the porous carbon-coated layered oxide positive electrode material obtained in step 2 in a chemical vapor deposition furnace, introduce 200 ml / min of nitrogen, raise the temperature to 1000°C, introduce carbon source gas (the carbon source gas in this embodiment is methane), and the ventilation rate is 200 ml / min. After reacting for 90 minutes, cut off the carbon source gas, and cool to room temperature under a protective atmosphere of nitrogen to obtain the corresponding screening-type sodium ion battery positive electrode material.

[0041] Example 3 The preparation method of the screening type sodium ion battery positive electrode material of this embodiment is the same as that of Example 1, except that the raw materials used and the parameter conditions involved in the preparation process are different (see Table 1). The mixing method of the precursor material in this embodiment is impregnation mixing, and the specific steps are:

[0042] Step 1: Prepare a carbon precursor into an aqueous solution at a concentration of 100M (the carbon precursor in this embodiment is polypropylene in a solid powder state), pour a layered metal oxide precursor (the layered metal oxide in this embodiment is the same as that in Example 1) into the aqueous solution at a mass ratio of 500:1 between the layered oxide precursor and the carbon precursor, and immerse for 6 hours. After filtering, dry the filter cake to obtain a composite precursor;

[0043] Step 2: placing the composite precursor obtained in step 1 in a tube furnace, and heat-treating it at 600° C. under a nitrogen atmosphere, to obtain a porous carbon-coated layered oxide positive electrode material after heat treatment for 4 hours;

[0044] Step 3: Place the porous carbon-coated layered oxide positive electrode material obtained in step 2 in a chemical vapor deposition furnace, introduce 200 ml / min of nitrogen, raise the temperature to 900°C, introduce carbon source gas (the carbon source gas in this embodiment is methane), and the ventilation rate is 500 ml / min. After reacting for 90 minutes, cut off the carbon source gas, and cool to room temperature under a protective atmosphere of nitrogen to obtain the corresponding screening-type sodium ion battery positive electrode material.

[0045] Example 4 The preparation method of the screening type sodium ion battery positive electrode material of this embodiment is the same as that of Example 1, except that the raw materials used and the parameter conditions involved in the preparation process are different (see Table 1). The mixing method of the precursor material of this embodiment is the same as that of Example 1, which is stirring and mixing. The specific steps are:

[0046] Step 1: Stir and mix a layered metal oxide precursor (the layered metal oxide in this embodiment is the same as that in Example 1) and a carbon precursor (the carbon precursor in this embodiment is polyacrylonitrile in a solid powder state) at a mass ratio of 500:1 to obtain a composite precursor;

[0047] Step 2: placing the composite precursor obtained in step 1 in a tube furnace, and heat-treating it at 600° C. under a nitrogen atmosphere, to obtain a porous carbon-coated layered oxide positive electrode material after heat treatment for 3 h;

[0048] Step 3: Place the porous carbon-coated layered oxide positive electrode material obtained in step 2 in a chemical vapor deposition furnace, introduce 200 ml / min of nitrogen, raise the temperature to 900°C, introduce carbon source gas (the carbon source gas in this embodiment is methane), and the ventilation rate is 200 ml / min. After reacting for 240 minutes, cut off the carbon source gas, and cool to room temperature under a protective atmosphere of nitrogen to obtain the corresponding screening-type sodium ion battery positive electrode material.

[0049] Example 5 The preparation method and raw materials of the screening type sodium ion battery positive electrode material of this example are the same as those of Example 1, except that the parameter conditions involved in the preparation process are different (see Table 1):

[0050] In the process of step 1 of this embodiment, the mass ratio of the layered oxide to the phenolic resin is 1000:1.

[0051] Example 6 The preparation method and raw materials of the screening type sodium ion battery positive electrode material of this example are the same as those of Example 1, except that the parameter conditions involved in the preparation process are different (see Table 1):

[0052] In the process of step 2 of this embodiment, the heat treatment temperature is 1000° C. and the time is 2 hours.

[0053] Example 7 The preparation method and raw materials of the screening type sodium ion battery positive electrode material of this example are the same as those of Example 1, except that the parameter conditions involved in the preparation process are different (see Table 1):

[0054] In the process of step 1 of this embodiment, the mass ratio of the layered oxide to the phenolic resin is 1:1.

[0055] Comparative Example 1

[0056] The difference between this comparative example and implementation 1 is that the layered oxide in this comparative example is not carbon-coated, but directly heat-treated at 600° C. and directly used as a positive electrode material after heat treatment for 3 hours.

[0057] Comparative Example 2

[0058] The difference between this comparative example and implementation 1 is that the layered oxide in this comparative example is only subjected to the porous carbon coating treatment of step 1 and step 2, and the vapor deposition treatment of step 3 is not performed.

[0059] Comparative Example 3

[0060] The difference between this comparative example and implementation 1 is that in the process of step 2, the heat treatment temperature is 1500° C. and the heat treatment time is 2 h.

[0061] Comparative Example 4

[0062] The difference between this comparative example and implementation 1 is that in the process of step 2, the heat treatment temperature is 500° C. and the heat treatment time is 4 hours.

[0063] Comparative Example 5

[0064] The difference between this comparative example and implementation 1 is that in the process of step 3 of this comparative example, the ventilation rate of the carbon source gas is 800 ml / min.

[0065] Comparative Example 6

[0066] The difference between this comparative example and implementation 1 is that in step 3 of this comparative example, the temperature of chemical vapor deposition is 1100°C.

[0067] Comparative Example 7

[0068] The difference between this comparative example and implementation 1 is that in the process of step 3 of this comparative example, the time of chemical vapor deposition is 360 minutes.

[0069] Comparative Example 8

[0070] The difference between this comparative example and implementation 1 is that in the process of step 3 of this comparative example, the ventilation rate of the carbon source gas is 5 ml / min.

[0071] Comparative Example 9

[0072] The difference between this comparative example and implementation 1 is that in step 3 of this comparative example, the temperature of chemical vapor deposition is 500°C.

[0073] Comparative Example 10

[0074] The difference between this comparative example and implementation 1 is that in the process of step 3 of this comparative example, the time of chemical vapor deposition is 20 minutes.

[0075] Table 1 Preparation process parameter conditions of examples and comparative examples

[0076]

[0077] Test Example 1

[0078] 1. Preparation of sodium ion button battery

[0079] The sieving type sodium ion battery positive electrode materials obtained in the embodiment and the comparative example were respectively prepared into sodium ion button batteries, and the preparation process was as follows:

[0080] (1) Preparation of positive electrode: The obtained sieve-type sodium ion battery positive electrode material, conductive carbon black (Super-P) with conductive function and polyvinylidene fluoride (PVDF) with bonding function were mixed in N-methylpyrrolidone (NMP) at a mass ratio of 8:1:1, the mixed material was coated on the surface of aluminum foil and then placed in an oven and vacuum dried at 110°C for 12 hours to obtain an electrode sheet, and the obtained electrode sheet was made into a circular electrode sheet with a diameter of 10 mm;

[0081] (2) Preparation of sodium ion button cell: A circular electrode sheet was assembled with sodium metal, 100 μL of a composite electrolyte (the electrolyte composition of this embodiment is ethylene carbonate, dimethyl carbonate and sodium hexafluorophosphate), and a separator to obtain a sodium ion half-cell.

[0082] 2. Performance Testing

[0083] The sodium ion button batteries prepared in the embodiment and the comparative example were respectively used for performance testing, and the test results are shown in Table 2:

[0084] Table 2 Performance test table of embodiments and comparative examples

[0085]

[0086] Result analysis:

[0087] It can be seen from the data in Table 2 that the screening-type sodium ion battery positive electrode material obtained by the method described in this embodiment has excellent performance, a reversible sodium storage capacity of up to 150-200 mAh / g, an initial coulombic efficiency of more than 90%, and can stably operate for more than 3500 cycles when the capacity retention rate is 80%.

[0088] Among them, the specific surface area of ​​the sieve-type sodium ion battery positive electrode material prepared according to the method of Example 1 is 5m 2 / g, used for sodium ion button battery testing, with a reversible sodium storage capacity of 200mAh / g, and a first coulombic efficiency of 93% (such as Figure 2 As shown, Figure 2From left to right, the low to high line is the first cycle charging curve, and the high to low line is the first cycle discharge curve, indicating that the first cycle charging capacity of the positive electrode is 215mAh / g, the first cycle discharge capacity is 200mAh / g, and the first coulomb efficiency is 93% (first coulomb efficiency = first discharge capacity / first charging capacity × 100%). Because the positive electrode battery is charged first and then discharged, the reversible sodium storage capacity is the first cycle discharge capacity). When the capacity retention rate is 80%, it can run stably for 4000 cycles (such as Figure 3 As shown), the comprehensive performance is excellent and it is the best embodiment of the present invention.

[0089] It can be seen from Examples 2-7 that changes in preparation conditions will affect the reversible sodium storage capacity, first coulombic efficiency and cycle stability of the final positive electrode material. Among them, the results of Examples 5 and 7 show that in the preparation of the composite precursor, the ratio of the layered oxide precursor to the carbon precursor will affect the quality of the composite precursor, resulting in a relative decrease in the comprehensive performance of the final positive electrode material. The results of Examples 2-4 and 6 show that the relative adjustment of the preparation parameter conditions within a certain range will affect the performance of the positive electrode material to a certain extent, but can still maintain good comprehensive performance.

[0090] The results of comparative examples 1-10 show that when the parameter conditions of the preparation process exceed the range described in the present invention, it is impossible to suppress the occurrence of side reactions on the positive electrode surface and the rapid transmission of ions, and the effect of the present application cannot be obtained.

[0091] Among them, comparative examples 1-4 did not undergo a chemical vapor deposition process, and the resulting screening-type sodium ion battery positive electrode materials exhibited lower reversible sodium storage capacity, lower first coulombic efficiency, and poorer cycle stability.

[0092] Among them, the surface of the layered metal oxide in comparative example 1 is not subjected to carbon coating treatment, and the layered metal oxide in comparative example 2 is directly used as the positive electrode material after heat treatment to obtain a porous carbon coating layer without vapor deposition treatment. The nitrogen adsorption and desorption test results of comparative example 2 and embodiment 1 are compared. Figure 4 As shown, the specific surface area of ​​the positive electrode material of Comparative Example 2, which was not subjected to the sieving treatment but only subjected to the porous carbon coating treatment, was 50 m 2 / g is significantly larger than the specific surface area of ​​the screening carbon in Example 1 by 5m 2 / g. It can be seen from the results of Comparative Example 1 and Comparative Example 2 in Table 2 that the positive electrode materials of both exhibit lower reversible sodium storage capacity, lower first coulombic efficiency and poor cycle stability.

[0093] In Comparative Example 3, the heat treatment temperature of the layered metal oxide is too high, and an ordinary nonporous carbon coating layer is obtained. The nonporous carbon is coated and is directly used as a positive electrode material without vapor deposition treatment. Although the initial coulombic efficiency and cycle stability are good, the lack of channels for rapid sodium ion transmission in the pore structure leads to a low reversible sodium storage capacity. In Comparative Example 4, the heat treatment temperature of the layered metal oxide is too low, and an ordinary nonporous carbon coating layer is obtained, which also cannot be vapor deposited.

[0094] It can be obtained from the results of Comparative Examples 3 and 4 that in the process of preparing the porous carbon material coating layer of the composite precursor, the temperature needs to be strictly controlled. If the temperature is too low, the carbonization is not complete and the pores cannot be introduced, which makes the material's ion conductivity weak, resulting in high transmission impedance and affecting the material's rate performance; if the temperature is too high, the pores are closed and the internal layered oxide will undergo a crystal transformation, resulting in a decrease in the reversible sodium storage capacity.

[0095] The results of Comparative Examples 1-4 show that the surface of the layered metal oxide needs to be coated, and the coating process needs to be strictly controlled. The resulting coating layer will affect the feasibility of the subsequent vapor deposition process, resulting in the final pore structure being unable to provide a good ion transfer rate, affecting the reversible sodium storage capacity and cycle stability.

[0096] Although comparative examples 5-7 underwent a chemical vapor deposition process, the resulting screening-type sodium ion battery positive electrode material still exhibited a low reversible sodium storage capacity, a low first coulombic efficiency, and a poor cycle stability. From the results of comparative examples 5-7, it can be seen that if any one of the carbon source gas introduction rate, temperature, and reaction time is too high, the pores will be completely blocked, and it will be impossible to provide a fast transmission channel for ions through the specific pore structure, resulting in a lower reversible sodium storage capacity.

[0097] From the results of Comparative Examples 8-10, it can be seen that if any one of the carbon source gas introduction rate, temperature and reaction time is too low, it will also affect the battery performance, cause the pores to be incompletely closed during the preparation process, and fail to form sieve-type pores, resulting in the electrolyte or humid air passing through the pores and contacting the layered metal oxide material, resulting in aggravated side reactions, and the ability to inhibit the occurrence of side reactions on the surface of the layered metal oxide positive electrode material and the dissolution of transition metals is not possessed, resulting in a decrease in the initial coulombic efficiency and cycle stability, affecting the service life of the battery.

[0098] In summary, it can be seen from the test results of the embodiments and comparative examples that the present invention is to coat the surface of the positive electrode with porous carbon and vapor-deposit the pores to obtain a screening carbon coating layer, so that it can effectively inhibit the occurrence of surface side reactions and the dissolution of transition metals while providing a good ion transfer rate. If the present invention is to achieve the effects of inhibiting side reactions and rapid ion transmission, the two processes of coating the surface of the layered metal oxide positive electrode with porous carbon and vapor-depositing the pores to obtain a screening carbon coating layer are indispensable, and the parameter conditions of the coating process and the chemical vapor deposition process need to be strictly controlled, and the parameters are relatively adjusted within a specific range. The obtained positive electrode material can still maintain good performance, but when the parameter conditions exceed a specific range, the obtained positive electrode material exhibits a lower reversible sodium storage capacity, a lower first coulomb efficiency, and a poorer cycle stability.

[0099] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any minor modifications, equivalent substitutions and improvements made to the above embodiments based on the technical essence of the present invention should be included in the protection scope of the technical solution of the present invention.

Claims

1. A method for preparing a sieving type sodium ion battery positive electrode material, comprising the preparation of a porous carbon-coated layered oxide positive electrode material and the preparation of a sieving type sodium ion battery positive electrode material, characterized in that: The porous carbon-coated layered oxide positive electrode material is prepared by subjecting a composite precursor of a layered oxide precursor and a carbon precursor to a heat treatment process; wherein the mass ratio of the layered oxide precursor to the carbon precursor is 1:1-500:1, and the temperature of the heat treatment process is 600°C; The screening type sodium ion battery positive electrode material is prepared by a porous carbon-coated layered oxide positive electrode material through a chemical vapor deposition process; the carbon source gas ventilation rate in the chemical vapor deposition process is 200-500 ml / min, the deposition temperature is 900° C., and the reaction time is 30-90 min; The layered oxide precursor is Na x TMO2 precursor, x≤1, TM is at least one of Ni, Co, Fe, Mn, Cu, and Zn; The carbon precursor is any one of phenolic resin, glucose, sucrose, polypropylene and polyacrylonitrile.

2. The method for preparing a screening type sodium ion battery positive electrode material according to claim 1, characterized in that: The carbon precursor is in the state of molten liquid or solid powder.

3. The method for preparing a screening type sodium ion battery positive electrode material according to claim 1, characterized in that: The specific steps include: Step 1: Stirring or impregnating a layered oxide precursor and a carbon precursor at a mass ratio of 1:1-500:1 to obtain a composite precursor; Step 2: placing the composite precursor obtained in step 1 in a tube furnace and performing heat treatment under a protective atmosphere of nitrogen or argon to obtain a porous carbon-coated layered oxide positive electrode material; Step 3: Place the porous carbon-coated layered oxide positive electrode material obtained in step 2 in a chemical vapor deposition furnace, introduce nitrogen or argon, heat it to the deposition temperature, introduce the carbon source gas, and after the reaction is completed, cut off the carbon source gas, cool it down to room temperature under a protective atmosphere of nitrogen or argon to obtain the screening-type sodium ion battery positive electrode material.

4. The method for preparing a screening type sodium ion battery positive electrode material according to claim 3, characterized in that: The impregnation and mixing process in step 1 is as follows: the carbon precursor is configured into an aqueous solution at a concentration of 0.1-100M, the layered oxide precursor is poured into the aqueous solution at a mass ratio of 1:1-500:1 to the carbon precursor, and the layered oxide precursor is immersed for 6-48 hours, and the filter cake is dried after filtering to obtain a composite precursor.

5. The method for preparing a screening type sodium ion battery positive electrode material according to claim 3, characterized in that: The heat treatment time in step 2 is 2-4 hours.

6. The method for preparing a screening type sodium ion battery positive electrode material according to claim 3, characterized in that: The carbon source gas in step 3 is any one of acetylene, benzene vapor, toluene vapor, xylene vapor, ethylene, methane, propane, and natural gas.

7. A screening type sodium ion battery positive electrode material, characterized in that: The preparation method is described in any one of claims 1 to 6.

8. Use of the screening type sodium ion battery positive electrode material according to claim 7 in a sodium ion battery.

Citation Information

Patent Citations

  • Carbon-coated sodium ion layered oxide positive electrode material and preparation method thereof

    CN116130617A

  • Coated sodium ion positive electrode material and preparation method and application thereof

    CN117080404A

  • Carbon material and conductive agent-free negative electrode

    CN117810432A